Modification of Fishbone-Based Hydroxyapatite with MnFe2O4 for Efficient Adsorption of Cd(II) and Ni(II) from Aqueous Solution - Poedji Loekitowati Hariani; Addy Rachmat; Muhammad Said; Salni Salni (Universitas Gadjah Mada, 2021)
Due to their toxicity, Cd(II) and Ni(II) ions in the environment are severe. The hydroxyapatite composite was improved with magnetic MnFe2O4 to remove Cd(II) and Ni(II) ions from an aqueous solution. Hydroxyapatite was extracted from Snakehead (Channa striata) fish bones via alkaline-heat treatment. The hydroxyapatite/MnFe2O4 composite performance was analyzed through XRD, FTIR, SEM-EDS, BET analysis, and VSM, and the results reveal that the hydroxyapatite/MnFe2O4 composite shows good magnetic properties of 21.95 emu/g. The kinetics evaluation confirmed that the pseudo-second-order kinetics model was more suitable to describe the adsorption of Cd(II) and Ni(II) ions by hydroxyapatite/MnFe2O4 composite from the solution. The Langmuir isotherm model was suitable to describe the adsorption process of the Cd(II) and Ni(II) ions, where the adsorption capacities for Cd(II) and Ni(II) are 54.3 and 47.4 mg/g, respectively. Desorption of Cd(II) and Ni(II) ions from hydroxyapatite/MnFe2O4 composite using NaCl as the eluent was more effective than EDTA. The findings of this study indicate that hydroxyapatite/MnFe2O4 can reduce Cd(II) and Ni(II) ions in wastewater so that it can recover natural resources.